2009
DOI: 10.1177/112070000901900209
|View full text |Cite
|
Sign up to set email alerts
|

Hip Resurfacing using the Trochanteric Flip Osteotomy

Abstract: We report the early results and complications of resurfacing arthroplasty using the 'Trochanteric Flip Osteotomy' approach to the hip. There are no published clinical results of this approach used for resurfacing arthroplasty. One hundred consecutive patients were assessed prospectively for a minimum follow-up of 2 years (range 2-5 years). The Oxford Hip Score fell from a median of 30 pre-operatively to 5 at two years. Similar improvement was found in the UCLA Activity Score. There were no cases of component f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The studies included one randomised, clinical trial, 27 prospective case series and one retrospective case series. [9][10][11][22][23][24][25][33][34][35][36][37][38][39][40][41][42][44][45][46][47][48][49][50][51][52][53][54][55] The mean follow-up ranged from 0.6 to 10.5 years. The highest reported loss to follow-up was 8.3% 50 and 11 studies reported no loss to follow-up.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies included one randomised, clinical trial, 27 prospective case series and one retrospective case series. [9][10][11][22][23][24][25][33][34][35][36][37][38][39][40][41][42][44][45][46][47][48][49][50][51][52][53][54][55] The mean follow-up ranged from 0.6 to 10.5 years. The highest reported loss to follow-up was 8.3% 50 and 11 studies reported no loss to follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…The highest reported loss to follow-up was 8.3% 50 and 11 studies reported no loss to follow-up. 11,22,25,34,35,42,48,49,[52][53][54] The survival of the implant ranged between 84% and 100% (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients of greater than 60 years of age, we suggest that an alternative, such as the posterior or modified anterolateral approach 4 should be used. Killampalli et al 2 reported four patients (4%) with pain due to the prominence of the screw heads in healed osteotomies that later required screw removal. Ganz et al 1 and Khan et al 4 did not comment on this complication in their papers.…”
Section: Audit-induced Change Reduces Complications Of the Ganz Nortomentioning
confidence: 99%
“…Metal on metal resurfacing (12,13,14,15,16,17,18) remains topical, and the associated issues relating to biomechanics (19,20) and blood supply (21). Advances in the early and late management of developmental dysplasia have been addressed (22,23,24,25,26), and new methods of imaging for this condition and femoro-acetabular impingement have been evaluated (27,28).…”
mentioning
confidence: 99%